Selection and validation of emotional videos: Dataset of professional and amateur videos that elicit basic emotions - Hong Yi Chen; Kai Ling Chin; Chrystalle B.Y. Tan (Elsevier Ltd, 2021)
This article describes the process of selecting a collection of professional and amateur videos that elicit five basic emotions (i.e., happiness, fear, disgust, anger, and sadness) and validating these videos in three groups of participants (i.e., Chinese from China, Chinese from Malaysia, and Bumiputera from Malaysia). In the video selection phase, professional videos, which were Western movie trailers, were selected from IMDb (Internet Movie Database) and amateur videos were selected from YouTube. The researchers selected videos that display five basic emotions, identified the time frames with the strongest display of emotion, and rated the emotional intensity of each video on a 5-point Likert scale. After the initial stage of selection, two other researchers performed an emotion recognition task by watching the videos without audio to ensure that the emotions can be elicited without understanding the language. This data was used to refine the final selection of 20 professional videos and 20 amateur videos. In the video validation phase, 30 participants were asked to identify and rate the intensity of emotion felt. This article includes a description of the video selection method, a detailed list of the videos selected, and participants' responses and ratings of emotional intensity for the 40 videos.